1986
DOI: 10.1177/002248718603700103
|View full text |Cite
|
Sign up to set email alerts
|

Deductions about Supportive Induction

Abstract: Although a great deal is understood rela tive to the concerns of beginning teachers, little is known of programs that effectively assist new staff members dur ing the crucial induction period. The authors propose a set of goals for teacher induction programs, with par ticular emphasis on the outcomes of re flection and self-assessrment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Taking into account the previously cited research findings and in consideration of recent writing by Galvez-Hjornevik (1986) on mentoring, Showers (1982Showers ( , 1984 on peer coaching, Fox and Singletary (1986) …”
Section: Mentor and Protege Relationshipsmentioning
confidence: 91%
“…Taking into account the previously cited research findings and in consideration of recent writing by Galvez-Hjornevik (1986) on mentoring, Showers (1982Showers ( , 1984 on peer coaching, Fox and Singletary (1986) …”
Section: Mentor and Protege Relationshipsmentioning
confidence: 91%
“…formal InductIon programs are necessary (Hall, 1982;GriffIn, 1985). Investigating the conditions in the workplace (Zeichner, 1982) and the impact of specific induction practices on the development of teachers (Hall, 1982;Zeichner, 1982;McCaleb, 1985) Although there was some type of formal orIentation for the seventy-two begInnIng teachers surveyed by Grant and ZeIchner (1981) Many authors have identified goals for induction programs (Fox & Singletary, 1986;Huling-Austin, 1986a;Varah, Theune, & Parker, 1986), provided detailed descriptions for beginning teacher induction programs (Hall. 1982;Tisher, 1982;Hoffman et al, 1985;Huling-Austin, 1985), and described the effect of certain induction programs (Hoffman, Edwards, O'Neal, Barnes, & Paulissen, 1986;Houston & Felder, 1986).…”
Section: Rationale and Descriptionmentioning
confidence: 99%
“…It is generally agreed that the nature of the support offered to new teachers should be consonant with their needs (Fox & Singletary, 1986). This implies that a valid Sandra J.…”
Section: Introductionmentioning
confidence: 99%